Pengembangan Media Pembelajaran Interaktif Budaya Lokal Banten Berbasis Teknologi Informasi untuk Meningkatkan Minat Belajar Siswa - Hilda Rosinta; Eko Wahyu Wibowo; Oman Farhurohman (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
The purpose of this study was to find out the procedures for media development, media feasibility testing, and student learning interest after using information technology-based interactive Banten local culture media. This research method is Research and Development (R&D) using the Lee & Owens development model. Data collection was carried out using questionnaires, interviews, observation and documentation. The research that was conducted on 24 respondents obtained the results of the due diligence by media experts achieving a result of 90%, which means that this product is in the very feasible category. While the assessment of material experts achieves 72% results, which means this product is in the proper category. The average score in the student learning interest questionnaire after using development media is 90.36%, which means that student learning interest is in the very high category. So, it can be concluded that information technology-based interactive Banten local culture media can increase student learning interest in Class IV social studies material.